Impact of a mass-media consumer awareness campaign on food safety behavior and behavioral determinants among women in Dire Dawa and Harar, Ethiopia - Madjdian, D.S.; Asseldonk, M. van; Talsma, E.F.; Amenu, Kebede; Gemeda, Biruk A.; Girma, S.; Roesel, Kristina; Grace, Delia; Knight-Jones, Theodore J.D.; Vet, E. de (Elsevier, 2024)
Food safety is a pressing public health challenge in urban informal markets in sub-Saharan Africa. This study assessed the potential effectiveness of a nine-months food safety multi-media behavior change campaign implemented in Dire Dawa and Harar, Ethiopia (June 2022-February 2023) that aimed to encourage women to choose intact (safe) tomatoes at markets and safely prepare at households. Campaign channels included door-to-door household visits by health extension workers, TV and radio advertisements, billboards, and social media posts. Consumer panel surveys assessed self-reported food safety behavior and related behavioral determinants (i.e., intentions, knowledge, attitudes, norms and agency) pre-and-post campaign, 12 months apart. The sample included 765 consumers at endline with an attrition rate of 28.5%. Mixed-effects linear and ordered logistic models estimated changes associated with prompted recall. Campaign recall was high with 78.3% recalling a minimum of one channel. Recall was associated with higher access to safe food purchasing (aOR 1.994) and preparation (aOR 1.654) information. door-to-door visits, radio, and TV advert recall were associated with safer buying behavior recall (0.520, 0.515, 0.515 unit increases resp.). Prompted recall was associated with a 0.921 unit increase in safe household food preparation scores, where door-to-door visits and billboard showed the strongest association. Recall increased odds of higher intent to buy intact tomatoes (aOR1.409); printed media recall related to a 1.314 unit increase in knowledge scores. Finally, recall was associated with higher perceived health benefits (aOR 1.546), social descriptive norms (aOR 1.458), and self-efficacy (aOR 2.5) regarding safe tomato practices. In conclusion, a mass media behavior change campaign has potential to empower consumers to choose safer food in informal markets. Door-to-door visits, TV, radio and print media were notably more effective than social media channels. Beyond enhancing consumer knowledge and behavior, broader efforts are vital for enhancing food safety in urban informal markets, including ensuring the availability and affordability of intact, clean tomatoes by engaging and motivating actors within the tomato value chain.